2022
DOI: 10.1128/spectrum.01671-21
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cytokine Levels in Plasma of Patients with SARS-CoV-2 Do Not Contribute to Pulmonary Microvascular Endothelial Permeability

Abstract: Lung vascular endothelial injury in SARS-CoV-2 patients is one of the most important causes of morbidity and mortality and has been linked to more severe complications including acute respiratory distress syndrome (ARDS) and subsequent death due to multiorgan failure. We have demonstrated that in eight consecutive patients with SARS-CoV-2, who were not selected for evidence of endothelial injury, the diluted plasma induced intense lung microvascular damage, in vitro .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Targeting C3aR and C5aR can prevent intrinsic lung inflammation and tissue damage from SARS-CoV-2. Kovacs-Kasa [ 69 ], 2022 Experimental cell HLMVEC Endothelial permeability measurement of HLMVEC exposed to plasma from SARS-CoV-2 patients ECIS C3aR and C5aR antagonists Non-severe, severe SARS-CoV-2 induced permeability is not affected by C3a or C5a inhibitors. Perico [ 68 ], 2022 Experimental HMEC-1 Endothelial cells exposed to SARS-CoV-2 derived spike protein 1 Immunofluorescence C3aR and C5aR antagonists Severe Endothelial dysfunction induced by SARS-CoV-2-derived S1 protein triggers exuberant complement deposition on activated microvascular endothelial cells C3a and, to a lesser extent, C5a, further amplify complement activation that fuels inflammation in response to S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting C3aR and C5aR can prevent intrinsic lung inflammation and tissue damage from SARS-CoV-2. Kovacs-Kasa [ 69 ], 2022 Experimental cell HLMVEC Endothelial permeability measurement of HLMVEC exposed to plasma from SARS-CoV-2 patients ECIS C3aR and C5aR antagonists Non-severe, severe SARS-CoV-2 induced permeability is not affected by C3a or C5a inhibitors. Perico [ 68 ], 2022 Experimental HMEC-1 Endothelial cells exposed to SARS-CoV-2 derived spike protein 1 Immunofluorescence C3aR and C5aR antagonists Severe Endothelial dysfunction induced by SARS-CoV-2-derived S1 protein triggers exuberant complement deposition on activated microvascular endothelial cells C3a and, to a lesser extent, C5a, further amplify complement activation that fuels inflammation in response to S1.…”
Section: Resultsmentioning
confidence: 99%
“…In particular C5a further amplified activation of the complement system, which contributed to inflammation in response to S1 [ 68 ]. However, in one experimental cell study, pulmonary microvascular endothelial cell permeability induced by SARS-CoV-2 was not affected by C3aR (SB SB290157) and C5aR (W54011) antagonists [ 69 ]. HMEC-1 exposed to COVID-19 serum showed significantly higher C5b-9 formation of the cell surface compared with control serum [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of proteomic profiles revealed downregulation of many cytokines, chemokines and growth factors in heat-inactivated plasma (Ayache et al, 2006). It was also demonstrated that plasma from patients hospitalised with acute SARS-CoV-2 infection decreased transendothelial resistance of human lung microvascular endothelial cells, but these destructive effects were susceptible to heat inactivation (Kovacs-Kasa et al, 2022). Finally, complement components can by themselves damage BBB.…”
Section: Discussionmentioning
confidence: 99%
“…146 147 and ROS production after tolllike receptor (TLR) activation, with viral RNA binding leading to endothelial cells injury and subsequent blood vessel leakage. 148 As direct mechanisms, Kovacs-Kasa et al 149 recently suggested that an unidentified heat-labile plasma factor different from thrombin, cytokines, and the complement factors C3a and C5a is responsible for the enhanced vascular permeability observed in SARS-CoV-2-infected patients. In this sense, Robles et al 150 recently demonstrated that the S spike protein of SARS-CoV-2 can directly enhance permeability in vitro and in vivo by interacting with the α5β1 integrin on endothelial cells.…”
Section: Sars-cov-2mentioning
confidence: 99%